2019
DOI: 10.1021/acs.chemmater.9b02318
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Water Structure and Catalyst–Electrolyte Interface on the Design of Water Splitting Catalysts

Abstract: Hydrogen production technologies have attracted intensive attention for their potential to cope with future challenges related to renewable energy storage and conversion. However, the significant kinetic barriers associated with the oxygen evolution reaction (OER), one of the two half reactions at the heart of water electrolysis, greatly hinder the sustainable production of hydrogen at a large scale. A wide variety of materials have thus been designed and explored as OER catalysts. In this perspective, we brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 103 publications
(224 reference statements)
1
61
0
Order By: Relevance
“…This observation is in agreement with a previous report by Bockris and Otagawa who found a linear trend between the OER activity and the activation energies measured for a wide variety of perovskites, as we recently discussed. 42,43 Now turning to the evolution of the apparent pre-exponential factor as a function of the OER activity, it is found to decrease concomitantly to the decrease of the activation energies. While the decrease of the apparent pre-exponential factor should result in a decrease of the OER activity (equation 3b), the effect associated with the decrease of the activation energy is predominant on the OER kinetics for these perovskites.…”
Section: Resultsmentioning
confidence: 98%
“…This observation is in agreement with a previous report by Bockris and Otagawa who found a linear trend between the OER activity and the activation energies measured for a wide variety of perovskites, as we recently discussed. 42,43 Now turning to the evolution of the apparent pre-exponential factor as a function of the OER activity, it is found to decrease concomitantly to the decrease of the activation energies. While the decrease of the apparent pre-exponential factor should result in a decrease of the OER activity (equation 3b), the effect associated with the decrease of the activation energy is predominant on the OER kinetics for these perovskites.…”
Section: Resultsmentioning
confidence: 98%
“…Unlike the 2D RP phase, the H + /Sr 2+ exchange in cubic or hexagonal perovskite such as SrIrO 3 would introduce significant lattice strain on the 3D IrO 6 -network and thus compromise the structural integrity of the parent phase, leading to a dissolution of the phase and a precipitation of amorphous IrO x compounds on its surface. 18 30 which consists of trigonal layers of edgesharing octahedra.…”
Section: Resultsmentioning
confidence: 99%
“…They further pointed out that the OER performance of the above-mentioned perovskites is eventually dominated by the electrochemically deposited IrO x •mH 2 O at their surfaces, rather than the perovskites themselves. [154,155] Similarly, with Ir(111), Ir (210), and Ir(210) as planar models, Maillard and co-workers concluded that surface oxidation trends to be a more stable one, which may be not related to the original surface atoms arrangement and oxidation state. [153] Figure 10.…”
Section: Surface Reconstructionmentioning
confidence: 99%
“…; 779 A g Ru+Pt −1 @1.51 V 28 h@10 mA cm −2 Pd@Ir3L [90] 0.1 m HClO 4 263 mV @10 mA cm −2 3.33 A mg Ir [174] 0.5 m H 2 SO 4 270 mV @10 mA cm −2 800-1600 A g Ru Co-RuIr alloy [104] 0.1 m HClO 4 235 mV @10 mA cm −2 solvation on the OER activity of catalysts. [155] Furthermore, more theoretical studies and experiment measurements are required to reveal the mechanisms of electrode-electrolyte interfaces for designing better catalysts for OER in acid.…”
Section: Importance Of Catalyst-electrolyte Interfacementioning
confidence: 99%